Human health implications from consuming eggs produced near a derelict metalliferous mine: a case study . Issue 6 (3rd June 2022) - Sartorius, Andrea; Johnson, Matthew; Young, Scott; Bennett, Malcolm; Baiker, Kerstin; Edwards, Paul; Yon, Lisa
Abstract: Lead pollution from metalliferous mines can have major environmental and health effects long after the mines have closed. Animals living near derelict mine sites can inadvertently ingest lead-contaminated soils, causing them to accumulate lead and potentially experience significant adverse health effects. Human food products, such as eggs, produced near metalliferous mines may also be contaminated with lead. The focus of this case study was to determine whether free-range chickens living near a derelict lead mine had high lead body burdens, whether they were producing eggs with elevated lead concentrations, and whether these eggs could be hazardous to human health. Soil samples and chicken egg, feather, blood, and bone samples were collected from a small farm near an abandoned metalliferous mine. The soil in and around the chicken pens contained lead concentrations that were elevated above established soil lead baseline concentrations. The lead concentrations in the chicken feather, blood, and bone samples were consistent with lead toxicity and indicated long-term, continuous exposure. Finally, the lead concentrations in the eggs were significantly greater than those found in commercial eggs. Based on previously established lead benchmark dose levels, humans, and in particular, children, could experience adverse health impacts if they routinely consumed these eggs. Environmental lead contamination continues to pose a major health risk for humans, and further research, understanding, and awareness are required to safeguard the public from the risks of consuming food produced near derelict mines.